I Just Wish They'd Ask the Right Questions About Sex: Working to Improve Sexual Health Communication With Older Adults - Megan T. Ebor; Madeline Y. Sutton (Health Science Reports)
ABSTRACT Background and Aims Sexual health among older adults (ages 50 and above) remains under‐addressed in clinical settings, often due to ageism and misconceptions about older adults being asexual. Despite high rates of sexual activity in this age group, healthcare providers rarely initiate discussions about sexual wellness, particularly related to HIV and STIs. This project aimed to explore how health communication tools, specifically film and reflexive exercises, can challenge implicit bias and improve provider comfort with sexual health conversations across the lifespan. Methods A 24‐min documentary film, Even Me, focusing on HIV wellness and prevention among older adults, was screened at a professional conference attended by sexual health clinicians and researchers. Participants first engaged in a word‐association activity reflecting on the phrase “82‐years‐old” to surface implicit associations with aging. After the film, attendees participated in a facilitated discussion and completed a Qualtrics‐based postevaluation survey (n = 35/50, 70% response rate). Results Initial word‐association responses revealed ageist stereotypes, including terms like “frail,” “bent,” and “almost dead.” Post‐screening dialogue reflected a shift in awareness and sparked robust conversations. Survey responses indicated that 65% of attendees lacked a standardized tool to assess sexual history in older clients. Many reported an intention to integrate sexual health screenings into their practice and to educate peers and students. Educators emphasized a need to normalize sexual health education for older adults in academic curricula. Conclusion Health communication films like Even Me, paired with self‐awareness activities, are promising tools to disrupt ageist assumptions and promote sexual health conversations among providers. Such interventions can help foster inclusive, routine clinical practices that support sexual wellness throughout the aging process.